Educational needs of nurses on medicine use, indications and optic surgery ‎techniques - fayezeh mazoji; fataneh mazoji; simin karimi; kobra salamikohan (Journal of Holistic Nursing and Midwifery)
Introduction: Today, nurses in order to implement successful nursing care need variety of ‎knowledge on techniques of surgery in different operations. By knowing the level of ‎knowledge and practice of nurses, their educational needs can be determined.‎